Cyberbullying under Criminal Law: A Comparative Analysis of Indonesian and Malaysian Legal Frameworks - Handina Sulastrina Bakhtiar; Ahmad Yusup (Veteran Law Review, 2026)
This study aims to analyse and compare the conception of cyberbullying under the criminal laws of Indonesia and Malaysia. This study employs a normative legal research method, also referred to as doctrinal legal research, with a prescriptive analytical approach. The approaches adopted in this study comprise a conceptual approach, a case approach, and a comparative approach. The findings indicate that Indonesia regulates cyberbullying indirectly through Law Number 11 of 2008 concerning Electronic Information and Transactions, including its subsequent amendments, as well as through the National Criminal Code. By contrast, Malaysia provides more specific provisions through the reform of its Penal Code. The main difference lies in the formulation of the elements of the offence and the applicable criminal sanctions. Malaysia tends to provide clearer and more specific regulation concerning cyberbullying, whereas in Indonesia the regulation remains relatively abstract, and law enforcement practices continue to rely primarily on the Electronic Information and Transactions Law, the Pornography Law, and the National Criminal Code.